Penggunaan Edmodo Dalam Perkuliahan Zoologi Invertebrata - Rifki Survani (UNIVERSITAS PGRI MADIUN, 2022)
Indonesia's local wisdom in utilizing medicinal plants for traditional medicine is very Gadgets that are used excessively are feared to have a negative impact on learning activities. Instead of banning the use of gadgets, it would be better if we use gadgets to support learning activities. One of the applications on gadgets that help in the learning process is Edmodo. This application is one of the many applications that can be used in E-learning. This study aims to describe student responses to the use of edmodo in improving learning outcomes in the Invertebrate Zoology course. This study uses a pre-experimental method with a pre-test posttest design. Based on the results of the study, it was found that Edmodo is considered effective as a media to support learning, Edmodo has functions and performances that support learning activities.